Decrease of the amount of fat in chocolate at constant viscosity by optimizing the particle size distribution of chocolate. (January 2022) - Deou, Janine; Bessaies-Bey, Hela; Declercq, Fabien; Smith, Paul; Debon, Stephane; Wallecan, Joel; Roussel, Nicolas
Abstract: The objective of this paper is the formulation of fat-reduced chocolate without affecting the viscosity of chocolate suspension. To achieve this objective, we control the rheological behaviour of dark chocolate suspension by optimizing the morphological properties (particle size distribution and maximum packing fraction) of sugar and cocoa powders. It is shown that the maximum packing fraction of cocoa and sugar powders can be predicted by the compressive packing model developed for the optimization of cement-based materials in the construction industry. Further an accurate control of maximum packing fraction by adding "fine" cocoa particles with mean diameter of few micrometres, well below the usual range in conventional chocolate, allows for the decrease of the amount of fat in dark chocolate without affecting viscosity. Then the viscosity of dark chocolate can be related to the solid volume fraction and the maximum packing fraction by a phenomenological Krieger-Dougherty type equation. Thus, new opportunities exist for reducing the fat content of chocolates. Graphical Abstract: ga1 Highlights: The principles of the rheology of concentrated suspensions can be applied to chocolate suspensions. Optimizing the particle size distribution of chocolate suspensions leads to an increase of its maximum packing fraction. The increase of the maximum packing fraction allows to decrease the fat content of chocolate at constant viscosity. A packing model can be used to predict the maximum packing fraction of chocolate suspensions.